HIERARCHICAL MODEL FOR ALTERNATIVE METHODS COMPARISON OF THE CIVIL PROTECTION ANALYSIS AND INFORMATION SYSTEM OPERATION - Barylo O.G. (Pressing Problems of Public Administration, 2017)
The paper raises the problem of ef cient managerial decision-making on the basis of timely, relevant and reliable information. The system of indicators has been proposed, and a hierarchical model for alternative methods comparison of the Civil Protection Analysis and Information System operation has been built on the basis of the method of hierarchy analysis. The methodology for estimating the methods of the Civil Protection Analysis and Information System operation and the calculation task have been developed.